Distribution and morphology of present-day glaciers on Kamchatka - A. Ya. Muraviev (Лëд и снег, 2020)
The current glacierization of the Kamchatka Peninsula includes 643 glaciers with a total area 769.48±48.34 km2. A variety of combinations of macro-relief factors, climate and volcanism caused irregular distribution of glaciers on the Peninsula, as well as the great variability of its characteristics in different areas. In quantitative terms, the prevailing glaciers here are the corrie (31.3%) and corrie-valley (12.8%) ones, but the largest areas are occupied by the transection-valley (26.6% or 204.42±7.56 km2) and the corrie-valley (16.5% or 126.78±9.77 km2) glaciers. The average area of the Kamchatka's glaciers is 1.2 km2, and it varies from 0.7 km2 in non-volcanic regions to 2.87 km2 in zones of active volcanism. The part of the largest (> 5 km2) glaciers in the total number of them and the total area is maximal (10.9 and 67.1%, respectively) in regions of active volcanism, and it is minimal (2.2 and 21.6%) in non-volcanic territories. As for the small glaciers (0.1–0.5 km2), the proportion of them in the total number and area is maximal (55.1 and 18.7%, respectively) in non-volcanic regions, and minimal (20.7 and 1.5%) in regions of active volcanism. The Kamchatka glacierization is characterized by various morphological types of glaciers. The transaction-valley glaciers cover the largest areas in regions of both the active volcanism (33.7% or 89.03±2.26 km2) and in non-volcanic ones (31.8% or 41.45±2.04 km2). In the regions of Quaternary volcanism, the dominating in areas are the corrie-valley glaciers (24.3% or 91.09±7.04 km2). The regions of active volcanism are characterized by the greatest variety of morphological types of glaciers. The largest part of the glaciation area of Kamchatka falls on the glaciers of the Western (24.7%), South-Western (22.3%) and Eastern (20%) exposures. But the glaciers of the Western (23%), North-Western (20.7%) and Eastern (15.1%) exposures are also predominant by quantity. The greatest vertical extent and average heights are characteristic of glaciers in areas of active volcanism, while the smallest ones occur in non-volcanic areas.